2019
DOI: 10.14499/indonesianjpharm30iss1pp58
|View full text |Cite
|
Sign up to set email alerts
|

Nanocurcumin Preparation for Reducing Vcam-1 and IL-6 in High Fat Diet-Induced Hyperlipidemic Rats

Abstract: Hyperlipidemia is a pathological condition due to lipid metabolism abnormalities. Increased and oxidized LDL in hyperlipidemia will trigger an inflammatory response and produce proinflammatory cytokines, such as vascular cell adhesion molecule-1 (VCAM-1) and Interleukin-6 (IL-6). Curcumin can be used as antioxidants, anti-inflammatory and antihyperlipidemia, but as it is practically insoluble in water, formulation of curcumin nanosuspension is made to improve the effects of curcumin therapy. This study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
1
3
0
1
Order By: Relevance
“…In the current study, the addition of dietary phytosomal curcumin significantly decreased the concentration of sVCAM-1 in HFD-C rats to levels not significantly different from those for ND rats, indicating that this phytosomal curcumin formulation is effective in reducing sVCAM-1 to normal levels in HFD-induced rats. An outstanding finding in the current study is that the degree of reduction in sVCAM-1 levels (53% reduction) in HFD-C rats is very comparable to that reported by Pradana et al (2019), while using nanocurcumin formulation (52.5 % reduction). These results can be very significant if translated to, and established in clinical settings.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In the current study, the addition of dietary phytosomal curcumin significantly decreased the concentration of sVCAM-1 in HFD-C rats to levels not significantly different from those for ND rats, indicating that this phytosomal curcumin formulation is effective in reducing sVCAM-1 to normal levels in HFD-induced rats. An outstanding finding in the current study is that the degree of reduction in sVCAM-1 levels (53% reduction) in HFD-C rats is very comparable to that reported by Pradana et al (2019), while using nanocurcumin formulation (52.5 % reduction). These results can be very significant if translated to, and established in clinical settings.…”
Section: Discussionsupporting
confidence: 81%
“…For instance, results from a human study have also shown that sVCAM-1 levels in obese people could be reduced by 1 g/day supplementation of curcumin complexed with piperine, for a period of 30 days (Saberi-Karimian et al, 2020). As for animal studies, Pradana et al (2019) experimented on Wistar rats on an HFD and described a reduction of sVCAM-1 concentrations by curcumin with nanoparticle formulations. In the current study, the addition of dietary phytosomal curcumin significantly decreased the concentration of sVCAM-1 in HFD-C rats to levels not significantly different from those for ND rats, indicating that this phytosomal curcumin formulation is effective in reducing sVCAM-1 to normal levels in HFD-induced rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Limfosit merupakan sel inflamasi kronis yang bersifat spesifik sebagai respons imun host terhadap adanya suatu jejas saat terjadi inflamasi yang bersifat kronis. 9 Limfosit akan mengaktifkan receptor activator of nuclear factor-κB ligand (RANKL) yang akan berikatan dengan receptor activator of nuclear factor-κB (RANK). Berikatannya RANKL pada RANK menyebabkan terjadinya diferensiasi dan aktivasi osteoklas sehingga jumlah osteoklas akan meningkat dan terjadi resorpsi tulang.…”
Section: Pendahuluanunclassified